DAMPAK SUBSIDI HARGA PUPUK TSP DAN UREA TERHADAP KONTRIBUSI PRODUKSI JAGUNG JAWA TIMUR PADA PRODUKSI JAGUNG NASIONAL - Warih Pramusinto; Yuli Haryati; Triana Dewi Hapsari (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2009)
Corn is one of the strategic commodities, which has an economic value and a wide opportunity to develop. Because of its role as primary carbohydrate and protein sources after rice, and as a basic material for industry. Recent years, the need toward corn products continually increases, which is in a line with the more increasing population growth and corn consumption. East Java is one of the biggest corn belts in Indonesia. For corn yields, there is a yield discrepancy between corn yield rates produced by farmers and research Institute. One of the causes is the high price of fertilizer. The government policy that is to subsidize the fertilizer price will help corn products produced by the farmers. The goals of this study are to know the development of corn product contribution in East Java toward national corn products, to explore the influence of subsidized prices of TSP and Urea fertilizers to corn products in East Java and to find out the impacts of government policy, to subsidize the fertilizer prices, toward corn product contribution in East Java. This research uses secondary data taken from the year 1985-2006 by using two-stage least square method (2SLS) and trend method. The results of this study indicate that: (1) the development of corn product contribution in East Java toward national corn products tends to decrease; (2) the subsidized price of TSP fertilizer gives a negative influence to corn products while the subsidized price of Urea fertilizer gives a positive influence to corn products; (3) the impact of subsidized price of TSP fertilizer can decline the corn product contribution in East Java while the impact of subsidizes price of Urea fertilizer can increase corn product contribution in East Java.Key Word: ekonometric model, corn , subsidized prices